Analisis Kepuasan Masyarakat terhadap Kualitas Pelayanan Kesehatan Puskesmas Cihara Kabupaten Lebak Tahun 2022 - Yuliaridha, Wika Descha; Roslan, Rosidi; Darmaja, Sobar (Jurnal Sehat Mandiri, 2023)
The aspect of community or patient satisfaction as a measure of the level of quality of health services, is a unique and complex phenomenon, which can be aligned or inconsistent with the professional code of ethics and quality standards set by the government. The purpose of this study was to determine and analyze public satisfaction with the quality of health services. The type of research used is quantitative research with descriptive methods. The population in this study were all patients/families of Cihara Health Center patients in Lebak Regency who were registered at the inpatient and outpatient counters during the study. The sample in this study were 50 respondents. Simple regression analysis method, validity test, reliability test, and t test (partial). The results showed that the t test was 12.060 > 2.01063, so Ho was rejected and Ha was accepted, so that it can be concluded that t count > t table, then there is a positive and significant influence from variable X (quality of health services) on variable Y (public satisfaction). ). In conclusion, 68% of patients consisting of outpatients, inpatients and patient families who visited the Cihara Inpatient Health Center felt dissatisfied with the health services provided by the Health Center staff. It is hoped that the Puskesmas will improve service quality, especially in terms of physical appearance (tangibles), responsiveness (responsiveness), and assurance (assurance).